Longitudinal spatial distribution of aedes aegypti (Diptera: Culicidae) during the yellow fever epidemic in Angola, 2016 - María del Carmen Marquetti Fernández; Troco Arletty2; Cani P; Yoenys Hidalgo Flores (Global Journal of Zoology - Peertechz Publications, 2019)
Background and aims: Angola is one of the countries included in the endemic areas of yellow fever transmission in Africa. The objective of this study was to obtain information about the longitudinal spatial distribution and the mainly breeding sites of Ae. aegypti in Angola during the yellow fever epidemic in Angola during 2016. Methods: Angola is located in the western region of Southern Africa. The country limited by the Atlantic Ocean in the west, in the north with the Republic of Congo and the Democratic Republic of Congo, in the eastern with the Republic of Zambia, and in the south with the Republic of Namibia. It is divided in 18 provinces. The sampling was carried out in 51 municipalities distributed in all provinces, in villages and neighborhoods with suspicious and confi rmed cases of yellow fever during February- October 2016. The number of houses inspected was 20 only one time during the months for to determine presence or absence of Aedes aegypti.